Hubungan Pengetahuan Keluarga Tentang Tindakan Pembedahan Dengan Tingkat Kecemasan Keluarga Pada Pasien Pre Operasi Di Rumkit TK.II R.W. Mongisidi Manado - Risdiyanto Risdiyanto; Bayu Dwisetyo (Pusat riset dan Inovasi Nasional, 2023)
Surgery is a treatment action with invasive techniques, namely opening the body part to be treated through an incision and ending with closure and suturing of the wound. Anxiety occurs as an emotional response process when the family feels fear, which is followed by several signs and symptoms such as tension, fear, and alertness. The purpose of this study was to determine the relationship between family knowledge about surgery and family anxiety levels in pre-operative patients at TK II Robert Wolter Mongisidi Hospital, Manado. This research uses descriptive analytic method with cross sectional approach. The statistical test is as many as 33 respondents using accidental sampling. Data was collected by using a questionnaire to each respondent and using the HARS (Hamilton Anxiety Rating Scale). Furthermore, the data that has been collected is processed using the SPSS version 16.0 computer program to be analyzed with the Chi-Square test with a significance value (α) of 0.05. The result of this study is that there is a relationship between family knowledge about surgery and the level of family anxiety in pre-operative patients at TK II Robert Wolter Mongisidi Hospital, Manado. p = 0.000 where the p value is smaller than = 0.05.